Designing Organizations for Dynamic Capabilities. (August 2016) - Felin, Teppo; Powell, Thomas C.
How can organizations put dynamic capabilities into practice? This article focuses on the power of organizational design, showing how managers can harness new organizational forms to build a capacity for sensing, shaping and seizing opportunities. Fast-moving environments favor open organization and self-organizing processes that quickly convert individual capabilities into actionable collective intellect. However, such self-organizing processes require managers to design and execute them. Using Valve Corporation as a case example, this article shows how new design principles—such as polyarchy, social proofs, and new forms of open organization—allow organizations to build dynamic capabilities for sustained innovation in dynamic environments.